Best $n$-Term Approximations by Λ-Methods in the Spaces $S_ϕ^p$ - Stepanets, O. I.; Shydlich, A. L. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We determine the exact values of the upper bounds of $n$-term approximations of $q$-ellipsoids by Λ-methods in the spaces $S_ϕ^p$ in the metrics of the spaces $S_ϕ^p$.